Molecular Dynamics and Docking of Biphenyl: A Potential Attachment Inhibitor for HIV-1 gp120 Glycoprotein - Teow, C.T.; Ismail, Salmah; Jung, M.T. (Pharmacotherapy Group, University of Benin, Benin City, 2014)
Purpose: To develop a new drug that inhibits viral attachment and entry for the treatment of HIV/AIDS patients.